MENGHADAPI GLOBALISASI EKONOMI: PANCASILA DAN KONSTITUSI 1945 SEBAGAI DASAR SIKAP INDONESIA - Azwar, T. Keizerina Devi; Desiandri, Yati Sharfina; Siagian, Putri Rumondang (Yayasan Amanah Nur Aman, 2025)
This research aims to address economic globalization based on Pancasila. This type of research is juridical research, drawn from a literature review. The results of this study conclude that Indonesia's most appropriate stance in facing economic globalization is to adhere firmly to the Pancasila ideology and the 1945 Constitution (especially the original text and the spirit of the economic articles therein) as the main guideline in all fields. Economic globalization is like a strong current that brings both opportunities and threats; to filter this current, Pancasila must be used as a filter and foundation in the formulation of every policy. Actively fighting for a just global economic order. A national stance does not mean isolation; Indonesia must instead participate in international forums to encourage reform of more balanced global rules. Thus, the ideals of Indonesian independence to contribute to creating world peace and social justice (the Preamble to the 1945 Constitution) can be realized. This stance is evident, for example, in Indonesia's support for WTO reform to take into account the interests of developing countries, and the G20 initiative for a fair global digital tax. Indonesia can be the moral voice of Pancasila in the midst of the global economic arena.